2016 International Conference on Indoor Positioning and Indoor Navigation (IPIN) 2016
DOI: 10.1109/ipin.2016.7743656
|View full text |Cite
|
Sign up to set email alerts
|

Indoor positioning using LTE signals

Abstract: This paper presents an experiment using real Long-Term Evolution (LTE) signals to extend positioning from outdoors to indoors. LTE signals are of interest for positioning applications because of their availability indoors, where GNSS signal reception is limited. Different approaches for time of arrival (TOA) extraction are evaluated for their positioning performance, combined with an extended Kalman filter (EKF) for movement tracking. The paper shows that the performance is surprisingly good, with high visibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Another category of LTE signal TOA estimator makes use of the SRA, e.g., ESPRIT, based on the channel frequency measurements (Li & Pahlavan, 2004). In Driusso et al (2017Driusso et al ( , 2016, a TOA estimation algorithm, named the ESPRIT and Kalman filter for time-of-Arrival Tracking (EKAT), using the CRS, was proposed to increase the robustness to multipath effects. Signal combination in multiple domains, i.e., time, frequency, spatial, and cell ID domains, was adopted for performance enhancement.…”
Section: Experiments Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another category of LTE signal TOA estimator makes use of the SRA, e.g., ESPRIT, based on the channel frequency measurements (Li & Pahlavan, 2004). In Driusso et al (2017Driusso et al ( , 2016, a TOA estimation algorithm, named the ESPRIT and Kalman filter for time-of-Arrival Tracking (EKAT), using the CRS, was proposed to increase the robustness to multipath effects. Signal combination in multiple domains, i.e., time, frequency, spatial, and cell ID domains, was adopted for performance enhancement.…”
Section: Experiments Testingmentioning
confidence: 99%
“…In Driusso et al. (2017, 2016), a TOA estimation algorithm, named the ESPRIT and Kalman filter for time‐of‐Arrival Tracking (EKAT), using the CRS, was proposed to increase the robustness to multipath effects. Signal combination in multiple domains, i.e., time, frequency, spatial, and cell ID domains, was adopted for performance enhancement.…”
Section: Review Of Performance Analysis Of the Toa‐based Positioning mentioning
confidence: 99%
“…Several code phase-based receivers have been proposed to obtain the pseudorange measurements from LTE signals [13,[26][27][28]. Analytical and experimental results have shown that the performance of these receivers significantly degrades in multipath environments, making them practically unusable in indoor environments [14,17,29]. In this section, a receiver structure is proposed, which exploits the carrier phase measurements of LTE signals.…”
Section: Lte Receiver Architecturementioning
confidence: 99%
“…fingerprinting-based indoor positioning, adaptive forward-backward greedy algorithm, feature selection, modified Jaccard index, subregion selection, signals of opportunity. Torres-Sospedra et al 2015;Xie et al 2016), or RSS of cellular towers (Driusso et al 2016). Such signals are location dependent features, many of which can easily be measured using a variety of mobile devices (e.g., smart phones or tablets).…”
Section: Introductionmentioning
confidence: 99%